2019
DOI: 10.1055/a-0916-8598
|View full text |Cite
|
Sign up to set email alerts
|

Implications of different guidelines for surveillance after serrated polyp resection in United States of America and Europe

Abstract: Introduction Because individuals with serrated polyps and adenomas are at increased risk of developing new polyps and colorectal cancer (CRC), surveillance after resection is justified. After adenoma resection, most international guidelines are consistent, but recommendations for surveillance after serrated polyp resection vary. The United States Multi-Society Taskforce on CRC (US-MSTF) base surveillance intervals on serrated polyp subtype (traditional serrated adenoma, sessile serrated polyp, hyperplastic pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…However, our results indicated a surveillance interval of approximately 3 years, regardless of the presence of SSL, and observed no significant difference in the risk of metachronous HRA/AA. Furthermore, a recent study reported that the serrated polyp subtype had a minimal effect on determining the surveillance interval 26 . Given these findings, it is reasonable to recommend a surveillance colonoscopy interval equal to that of the similar adenoma risk group, irrespective of the presence of synchronous SSL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our results indicated a surveillance interval of approximately 3 years, regardless of the presence of SSL, and observed no significant difference in the risk of metachronous HRA/AA. Furthermore, a recent study reported that the serrated polyp subtype had a minimal effect on determining the surveillance interval 26 . Given these findings, it is reasonable to recommend a surveillance colonoscopy interval equal to that of the similar adenoma risk group, irrespective of the presence of synchronous SSL.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study reported that the serrated polyp subtype had a minimal effect on determining the surveillance interval. 26 Given these findings, it is reasonable to recommend a surveillance colonoscopy interval equal to that of the similar adenoma risk group, irrespective of the presence of synchronous SSL.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the high interobserver variation in serrated polyp classification [74 -77], the risk of inaccurate histologic subclassification of serrated polyp is substantial and undesirable. In addition, a recent study demonstrated that the effect of taking into account serrated polyp subtype in surveillance guidelines is only marginal, and resulted in different surveillance intervals in only 2 % of screened patients compared to a surveillance guideline not taking into account the serrated polyp subtype [78]. Therefore, to prevent undertreatment due to misclassification of serrated polyps, we recommend not to consider the serrated polyp subtype when choosing colonoscopy surveillance intervals.…”
Section: Serrated Polyps In Patients Requiring Surveillancementioning
confidence: 99%
“…This idea has been also shown by a study comparing the ESGE 2013 guideline 12 with the USMSTF 2012 21 focusing on the influence of serrated lesions. The assignment to the “3-year surveillance” group was the same regardless of the existence of SSLs because of the concurrence of advanced adenomas or three or more non-advanced adenomas 14 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, ESGE and USMSTF guidelines treat sessile serrated lesions (SSLs) differently, USMSTF guidelines considering specifically the number and size of SSLs 9 12 13 . These differences could have also an influence on surveillance intervals, but the evidence on the importance of SSLs in the planning of post-polypectomy follow-up is scarce 14 .…”
Section: Introductionmentioning
confidence: 99%